2017
DOI: 10.26421/qic17.13-14
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Using the tool of concatenated stabilizer coding, we prove that the complexity class QMA remains unchanged even if every witness qubit is disturbed by constant noise. This result may not only be relevant for physical implementations of verifying protocols but also attacking the relationship between the complexity classes QMA, QCMA and BQP, which can be reformulated in this unified framework of a verifying protocol receiving a disturbed witness. While QCMA and BQP are described by fully dephasing and depolarizi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The output amplitudes of a quantum circuit, as a quantum mechanical system, can likewise be described as the sum over all trajectories of the system. However, as quantum gates are typically modelled as operators on a finite dimensional Hilbert space, a discrete sum rather than integral is typically used [8,12,21,24].…”
Section: The Path-sum Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The output amplitudes of a quantum circuit, as a quantum mechanical system, can likewise be described as the sum over all trajectories of the system. However, as quantum gates are typically modelled as operators on a finite dimensional Hilbert space, a discrete sum rather than integral is typically used [8,12,21,24].…”
Section: The Path-sum Frameworkmentioning
confidence: 99%
“…In this work we propose a novel framework for the formal specification and functional verification of unitary (i.e., measurement-free) quantum circuits over a universal gate set -specifically, the Clifford group extended with Z-axis rotations taken from the Clifford hierarchy [17]. Our framework is built around Richard Feynman's path integral technique, which has been used recently to prove results in complexity theory [12,24], and to perform circuit simulation [10,21] and optimization [1,2,4]. Specifically, we develop a concrete representation of quantum operators as path-sums -exponential sums of basis states over a finite set of Boolean path variables.…”
Section: Introductionmentioning
confidence: 99%
“…As there are three stabilizers, we need three rounds of checks. By symmetry, it suffices to explain how to measure (CZ) 12 [27][28][29].) Take k independent output CCZ states from the quadratic protocol in the previous subsection, and separate a single qubit from each of the CCZ states.…”
Section: Quartic Error Reductionmentioning
confidence: 99%
“…Proof of Proposition 7. It has been shown that there exists some quantum channel N * ∈ MIO but not IO, i.e, there exists some quantum state ρ such that N * (ρ) = M(ρ) for any M ∈ IO [61], which implies that max…”
Section: Appendix D: Improvement From Coherent States In Channel Disc...mentioning
confidence: 99%